Disability and Borderline Personality Disorder in Chronic Pain Patients - Randy A Sansone; J David Sinclair; Michael W Wiederman (Pain Research and Management)
BACKGROUND AND OBJECTIVE: Few studies have examined the relationship between disability and borderline personality symptomatology, and, among those that have, findings have been inconsistent. In the present study, the relationship between medical disability and borderline personality symptomatology was examined in a sample of chronic pain patients.